Embryo transfers between C57BL/6J and DBA/2J mice: Examination of a maternal effect on ethanol teratogenesis - Gilliam, David (Frontiers in Genetics, 2014)
Genetic factors influence Fetal Alcohol Spectrum Disorders (FASD) in both humans and animals. Experiments using inbred and selectively bred mouse stocks that controlled for 1) ethanol dose, 2) maternal and fetal blood ethanol levels, and 3) fetal developmental exposure stage, show genotype can affect teratogenic outcome. Other experiments distinguish the teratogenic effects mediated by maternal genotype from those mediated by fetal genotype. One technique to distinguish maternal versus fetal genotype effect is to utilize embryo transfers. This study is the first to examine ethanol teratogenesis - fetal weight deficits and mortality, and digit, kidney, and vertebral malformations - in C57BL/6J (B6) and DBA/2J (D2) fetuses that were transferred as blastocysts into B6 and D2 dams. We hypothesized that, following maternal alcohol exposure, B6 and D2 fetuses gestating within B6 mothers, as compared to D2 mothers, will exhibit a higher frequency of malformations. On day 9 of pregnancy, females were intubated (IG) with either 5.8 g/kg ethanol (E) or maltose dextrin (MD). Other females were mated within strain and treated with either ethanol or maltose, or were not exposed to either treatment. Implantation rates were affected by genotype. Results show more B6 embryos implanted into D2 females than B6 females (p<.05; 47% vs 23%, respectively). There was no difference in the percentage of D2 embryos implanting into B6 and D2 females (14% and 16%, respectfully). Litter mortality averaged 24% across all experimental groups. Overall, in utero ethanol exposure reduced mean litter weight compared to maltose treatment (E=1.01 g; MD=1.19 g; p<.05); but maltose exposed litters with transferred embryos weighed more than similarly treated natural litters (1.30 g vs 1.11 g; p<.05). Approximately 50% of all ethanol exposed B6 fetuses exhibited some malformation (digit, vertebral, and/or kidney) regardless of whether they were transferred into a B6 or D2 female, or were naturally conceive